Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Biro Pembangunan Dan Lingkungan Hidup Provinsi DKI Jakarta - Tyas, Eliana Wahyuning; Ruminta, Darkiman; Akbar, Dudi Duta (CV Warnak Johanna Nusantara, 2026)
This research was conducted at the DKI Jakarta Province Development and Environment Bureau which has authority over various areas of development and environmental issues. This institution is tasked with coordinating, formulating, and evaluating policies in these various areas. The purpose of this research is to determine the effect of work motivation and work environment on employee performance at the DKI Jakarta Province Development and Environment Bureau. This research method uses a quantitative approach with a survey method through questionnaire distribution. The data used are primary and data collection uses saturated samples. Data analysis techniques include validity, reliability, normality, multicollinearity, heteroscedasticity, hypothesis testing and coefficient of determination tests processed using SPSS version 25. The results of the study indicate that partially, each variable has a positive and significant influence on employee performance, namely 0.001 (Work Motivation) and 0.008 (Work Environment). Simultaneously, the combination of the two also provides a positive and significant influence, namely 0.000. Thus, it can be concluded that both individually and together, the variables of work motivation and work environment contribute to improving employee performance